Fabrication of built-in retractable hose mechanism for domestic usage - Mustapa, Muhammad Wazir (2017)
Industry hose is one of the common product that have been used in all places. However, the usage of the product could affect the property such as hose damage, poor hose cleanliness and limit the hose life span. Nowadays, the retractable mechanism is one of the common mechanism used in daily life. There is some improvement can be done to the design itself to fulfil the daily activity. This report presents the methods to design the conceptual of built-in hose mechanism, and then to perform necessary analysis and finally fabricate the chosen mechanism. Existing design was studied for upgrading to a new efficient design. Three concepts of mechanism were compared based on the type of mechanism used and sketched. One from the concepts is selected and designed by using Pahl and Beitz design process. The design was drawn and analysed by the help of Solidworks software. The design then successfully fabricated based on the criteria selected and tested. At the end, a set of information on related design evaluation to be analysed according to the study. Built-in retractable hose mechanism can be applied on hose usage in industrial area. From the research and methodology conducted, the new design had successfully been fabricated to be used for domestic usage.